On closed-section wind-tunnel aeroacoustic experiments with a two-dimensional lifting body - Amaral, Filipe Ramos do; Pagani, Carlos do Carmo [UNESP]; Himeno, Fernando Henrique Tadashi; Souza, Daniel Sampaio [UNESP]; Medeiros, Marcello Augusto Faraco de (Elsevier, 2019)
Slat noise experiments are sometimes performed to provide data for the validation of numerical procedures. Under such circumstances, closed-section wind-tunnels, in contrast with open-section ones, offer well-defined boundary conditions for simulations. Nevertheless, many difficulties arise in aeroacoustic experiments with two-dimensional lifting body tests in such wind-tunnels. Reverberation and acoustic images can also interfere with the measurements. This paper addresses the effects of the aforementioned issues on the MD30P30N airfoil slat aeroacoustic measurements. Conventional beamforming and DAMAS deconvolution techniques were employed for the acoustic data post-processing. Pressure taps were used in the assessment of spanwise and chordwise pressures on the high-lift airfoil model surfaces. The interaction between the airfoil and the wind-tunnel wall boundary-layer was mitigated by the application of suction on the tunnel wall and rendered a more two-dimensional flow. Acoustic polyurethane -based foam was applied on the test-section walls for reducing reverberation effects on the slat noise source maps. The results showed the error in the noise spectrum associated with the three-dimensional effect at the model ends may correspond to a decrement of 4 deg or higher of the entire wing angle of attack. The acoustic treatment over the wind-tunnel closed-section walls mitigated the mirror sources, nevertheless, the effects of such source images on both noise source maps and noise spectra in the region of interest were considered small.
Keywords: Acoustic beamforming; Boundary-layer suction; Closed-section wind-tunnels; DAMAS; Slat noise; Wall acoustic treatment